Effect of a Triterpenoid-Rich Olive Oil on Chronic Kidney Disease in an Experimental Model of Diabetes Mellitus - De-la-Cruz-Cortés, José Pedro; Osuna-Esteban, Laura; Rodríguez-Pérez, María Dolores; Ortega-Hombrados, Laura; Sánchez Tévar, Ana María; Martín Aurioles, Esther; Fernández-Prior, María África; Pérez-Burillo, Sergio; Espejo-Calvo, Juan Antonio; González-Correa, José Antonio (MDPI, 2024)
The aim of this study was to assess the effect of triterpenoids on the development of diabetic nephropathy in an experimental model of diabetes mellitus. For this purpose, a destoned and dehydrated olive oil (DDOO) was used, comparing its effects to a destoned olive oil (DOO). DDOO had a higher triterpenoid content than DOO but an equal content of alcoholic polyphenols. Four study groups (n = 10 animals/group) were formed: healthy rats, diabetic control rats (DRs), and DRs treated orally with 0.5 mL/kg/day of DOO or DDOO for two months. DRs showed impaired renal function (proteinuria, increased serum creatinine, decreased renal creatinine clearance) and morphology (glomerular volume and glomerulosclerosis). These alterations correlated with increased systemic and renal tissue oxidative stress and decreased prostacyclin production. DDOO administration significantly reduced all variables of renal damage, as well as systemic and renal oxidative stress, to a greater extent than the effect produced by DOO. In conclusion, triterpenoid-rich olive oil may prevent kidney damage in experimental diabetes mellitus
Keywords: Nefropatías diabéticas; Diabetes; Nephropathy; Olive oil; Triterpenoids; Oxidative stress; Protascyclin